Peranan Notaris dalam Kepastian Hukum Prinsip Pemilik Manfaat (Beneficial Ownership) Berdasarkan Permenkumham Nomor 13 Tahun 2018 - M. Haris Hasyim; Rusdianto Sesung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The increasingly rapid development of globalization will have good and even bad impacts on social life. This is in line with the process of the birth of a legal entity which confirms the evidence that law involves several stages, and the role of a notary is crucial in the initial stages of forming a legal entity. Beneficial Ownership can be a serious issue in the business world. A beneficial owner is an individual or entity who ultimately owns, controls, or obtains economic benefits from a company or business entity. In Indonesia, BO is regulated in the Minister of Law and Human Rights Regulation (Permenkumham) Number 13 of 2018. The aim of this research is to explain the role of notaries in legal certainty regarding the principle of beneficial ownership based on Permenkumham Number 13 of 2018. The research method uses descriptive , namely research that describes or explains the problems discussed. The results of this research are that based on Government Regulation Number 13 of 2018 concerning the Actual Beneficial Owners of Corporations, this is a regulation that stipulates the obligation to record and report information regarding the beneficial owners of a company. Notaries have the obligation to record information regarding beneficial owners in the deed of establishment of a company. This information includes the name, identification number, address and amount of ownership of the beneficial owner. The role of a notary in the principle of beneficial ownership covers various aspects that support legal certainty and transparency in the ownership of a company or business entity.